2023
DOI: 10.1088/1367-2630/accec3
|View full text |Cite
|
Sign up to set email alerts
|

Defect induced nonequilibrium quantum dynamics in an interacting Bose–Hubbard flux ladder

Abstract: The interacting Bose-Hubbard flux ladder provides an ideal model to probe novel quantum phenomena of many-body systems. Here, we report on the first direct observation of dynamical quantum phase transition (DQPT) in interacting Bose-Hubbard flux ladder induced by defect perturbation, which provides a new scheme for experimental design and manipulation of the DQPT in ultracold atomic system. Under the mean-field approximation, DQPT is identified by resolving the order parameter and the temporal evolution of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Considering the left-right leg degree of freedom of the ladder system as an effective spin, the magnetic field locks spin and momentum of the particle, resulting in an effective spin-orbit interaction and leading to well-defined edge modes with chirality [35,36]: the atoms in the two legs move in opposite direction. Under an external perturbation, the magnetic ladder system exhibits rich chiral dynamics, such as chiral Bloch oscillation (BOs), superfluidity, coherent transformation, Landau-Zener tunneling [37][38][39][40][41], Landau-Zener-Stuckelberg-Majorana interferometry [42,43], nonequilibrium quantum dynamics [44], etc. Among them, the BOs, observed in many physical systems, including semiconductor superlattices [45] and ultracold atoms [46][47][48][49][50][51], are of great significance for study of band structures and their topological properties of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the left-right leg degree of freedom of the ladder system as an effective spin, the magnetic field locks spin and momentum of the particle, resulting in an effective spin-orbit interaction and leading to well-defined edge modes with chirality [35,36]: the atoms in the two legs move in opposite direction. Under an external perturbation, the magnetic ladder system exhibits rich chiral dynamics, such as chiral Bloch oscillation (BOs), superfluidity, coherent transformation, Landau-Zener tunneling [37][38][39][40][41], Landau-Zener-Stuckelberg-Majorana interferometry [42,43], nonequilibrium quantum dynamics [44], etc. Among them, the BOs, observed in many physical systems, including semiconductor superlattices [45] and ultracold atoms [46][47][48][49][50][51], are of great significance for study of band structures and their topological properties of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the dynamic research of the magnetic ladder system, it is shown that there are also abundant nonlinear dynamic characteristics in this system, e.g. chiral Bloch-Zener dynamics, Stückelberg interference, critical slowing down of the collective modes, dynamics supersolidlike phases, and nonequilibrium quantum dynamics [36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%